Analisis Potensi Daerah dalam Rangka Menghadapi Masyarakat Ekonomi Asean - Marius Masri (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2017)
Considering the establishment of Asean Economic Comunity is (i) the potential of lowering production expense in ASEAN cost 10-20 percent for goods consumption as an impact of economic integration; (ii) Raising competence of the region with standart implementation and international practic, intelectual property rights and competition. The purpose of this research is (i) to analyze the development of PDRB for 5(five) years (year 2010-2015) (ii) To analyze basic economis sector (superior) which can increase the effort of the region to compete in Asean Economic Comunity, (iii) To analyze potential economic sectors which is improved to suport economic development in Kupang City, and (iv) To find out to obstacles the government of Kupang City to cope with Asean Economic Comunity. Confronting to Asean Economic Comunity, the goverment of Kupang City make a program to incrase competition efforts to give some aid to all of businessmen, to improve the infrastructure, to raise the investation climate, and a program to increase human resource.